CAUSES OF PROLIFERATION OF SMALL ARMS AND LIGHT WEAPON ON NATION BUILDING ON THE PEOPLE OF UROMI (1970-1991) - Esezobor Paul; Fidelis Achoba (International Studies Journal)
The research work focus on the origin and brief history of Esanland in Edo State. This study examined proliferation of small arms and it impact on nation building in Esanland with special focus on Uraomi from 1970-1991. The research looks at the Esanland people, environment, causes and spread of small arms and lights weapon proliteration. This study investigated the proliferation of small arms and light weapons on nation building in Esanland in Edo State. Both primary and secondary sources were used for the collection of data.  The research work argued that the proliferation and use of illegal arms increases the frequency of violence in Eanland in Edo State of Nigeria as is as result of the end of the Nigeria civil war in 1970. This encourage or bring into Esandland difference people of different background which results in the spread of small arms and light weapon and led destruction of lives and properties. It is important for the government to check the spread and movement of small arms and light weapon in Esanland in Edo State or else street gangs, lawlessness individuals would create condition for anarchy in Edo and Nigeria at large. Government’s monopoly of arms and the security forces would be overwhelmed and unorganized groups and armed militias will constitute threat to the development of citizens of not only Esanland in Edo State but Nigeria as a whole.